Ancestral state reconstruction of ontogeny supports a bilaterian affinity for Dickinsonia. Issue 6 (23rd October 2015) - Gold, David A.; Runnegar, Bruce; Gehling, James G.; Jacobs, David K.
SUMMARY Despite numerous attempts, classification of the Precambrian fossil Dickinsonia has eluded scientific consensus. This is largely because Dickinsonia and its relatives are structurally simple, lacking morphological synapomorphies to clarify their relationship to modern taxa. However, there is increasing precedence for using ontogeny to constrain enigmatic fossils, and growth of the type species Dickinsonia costata is well understood. This study formalizes the connection between ontogeny in Dickinsonia—which grows by the addition of metameric units onto one end of its primary axis—with terminal addition, defined as growth and patterning from a posterior, subtermial growth zone. We employ ancestral state reconstruction and stochastic character mapping to conclude that terminal addition is a synapomorphy of bilaterian animals. Thus, terminal addition allies Dickinsonia with the bilaterians, providing evidence that large stem‐ or crown‐group bilaterians made up a significant proportion of the Precambrian biota. This study also illustrates the potential for combining developmental and phylogenetic data in constraining the placement of ancient problematic fossil taxa on the evolutionary tree.